COVID-19-Related Giant Coronary Aneurysms in an Infant with Multisystem Inflammatory Disorder in Children: The First Case Report from the United Arab Emirates and the Arab Region. (19th January 2021) - Ghatasheh, Ghassan; Al Dhanhani, Huda; Goyal, Ashutosh; Noureddin, Muhammad Bassel; Al Awaad, Doaa; Peerwani, Ziad
Abstract : Background . Multisystem inflammatory disorder in children and adolescents is a relatively new and rare complication of COVID-19. This complication seems to develop after the infection rather than during the acute phase of COVID-19. The clinical features are similar to a well-known inflammatory syndrome in children, Kawasaki disease, and it can lead to collapse and multiple organ failure requiring intensive care. The COVID-19-associated multisystem inflammatory syndrome in children and adolescents is referred to mutually as pediatric inflammatory multisystem syndrome temporally linked with SARS-CoV-2 (PIMS-TS) or multisystem inflammatory syndrome in children (MIS-C) correlated with COVID-19, and here, it is referred to as MIS-C. Case Presentation . This report describes a nine-month-old Asian infant presented with a two-week history of fever with nonspecific signs of viral illness and erythematous rash. The clinical and biochemical findings were compatible with complicated typical Kawasaki disease (KD). The infant fulfilled the World Health Organization criteria for MIS-C and was treated with intravenous immunoglobulin and anticoagulation, which he responded well to. He was discharged home in good condition after almost 3 weeks of treatment. Conclusion . This case highlights a rare but new phenomenon attributed to severe acute respiratory syndrome coronavirus 2 infection. We report the first case report of MIS-C in the United Arab Emirates and Arab region. Among KD's complications, massive aneurysm with thrombosis is rare and usually will have deleterious results if not diagnosed and managed promptly.